Attracting customers through practising gender in call-centre work. (1st July 2009) - ,
Abstract : The aim of this paper is to demonstrate and analyse various ways in which gender is used as a resource when call-centre firms and their employees create customer relationships. Drawing on interviews in a case study call centre it argues that men and women are understood to work differently from the point of view of attracting customers. Men are found important as individuals and through technology-related services, whereas women are conceived as resources through their association with certain products, not as individuals. Thus female gender as a resource is embedded in the commodified products.